2017
DOI: 10.4314/sajas.v47i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of CSN1S2 in South African dairy goat populations

Abstract: Alpha-s 2 casein has a significant influence on protein content in goat milk, and the technological properties important for cheese processing. Specific alleles (A, B, C, E and F) of the alpha (α) s2 -casein gene (CSN1S2) result in higher protein, casein and fat content, and improved coagulation properties, which are useful for improved cheese making. The aim of this study was to investigate the polymorphism and genetic variation of CSN1S2 in South African dairy goats, using DNA sequencing technology. Sixty da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(33 reference statements)
1
1
0
Order By: Relevance
“…A previous study on Indian and Turkish goats (Chessa et al, 2007) reflected the same trend, with high frequencies of the A allele in the majority of the analyzed populations. With regard to the CSN1S2 and CSN2 genes, we found that the A and C alleles, respectively, were predominant, a finding consistent with what has been published in European, African, Turkish, and Indian goats (Sacchi et al, 2005;Caroli et al, 2006Caroli et al, , 2007Chessa et al, 2007;Gigli et al, 2008;Vacca et al, 2014;Tortorici et al, 2014;Kusza et al, 2016;Grobler et al, 2017). In the CSN3 gene, the A and B alleles were predominant in most populations (Table 1), as previously published in a broad array of caprine breeds (Yahyaoui et al, 2003;Prinzenberg et al, 2005;Caroli et al, 2007;Chessa et al, 2007;Kiplagat et al, 2010;Di Gerlando et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…A previous study on Indian and Turkish goats (Chessa et al, 2007) reflected the same trend, with high frequencies of the A allele in the majority of the analyzed populations. With regard to the CSN1S2 and CSN2 genes, we found that the A and C alleles, respectively, were predominant, a finding consistent with what has been published in European, African, Turkish, and Indian goats (Sacchi et al, 2005;Caroli et al, 2006Caroli et al, , 2007Chessa et al, 2007;Gigli et al, 2008;Vacca et al, 2014;Tortorici et al, 2014;Kusza et al, 2016;Grobler et al, 2017). In the CSN3 gene, the A and B alleles were predominant in most populations (Table 1), as previously published in a broad array of caprine breeds (Yahyaoui et al, 2003;Prinzenberg et al, 2005;Caroli et al, 2007;Chessa et al, 2007;Kiplagat et al, 2010;Di Gerlando et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…To date, two studies have been performed to characterize casein in the SA goat breeds, one on κ-casein [46] and another on αS2-casein [47]. The first study investigated indigenous, Boer and Saanen goats using restriction fragment length polymorphism (RFLP) and DNA sequencing.…”
Section: Dairy Goatsmentioning
confidence: 99%